Calculators and Computers in the Classroom Select Summaries of Current Education Topics. Know-Pak No. 17 - Moursund, David; East, Phillip; Oregon State Dept. of Education, Salem ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1979)
The usage and availability of calculators, computers, and related instructional materials are presented. This publication is a Know-Pak, a summary of materials and articles that is part of a series of information packets developed by the Oregon Department of Education. Topics covered include: (1) a forecast of a computer literacy crisis in American education; (2) model goals for computer education; (3) sample program course and instructional goals; (4) computer use in Oregon; (5) computer and calculator terminology; (6) calculator use in elementary schools; (7) available textbooks; (8) sample problems; and (9) lists of current computer assisted instruction projects. Annotated bibliographies on articles from the "Oregon Computing Teacher," selected summarized reports from the Oregon Council for Computer Education, and other sources of information such as publications, organizations, and people active in Oregon's computer education programs are also included. (MP)
Educational level discussed: Elementary Secondary Education.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Annotated Bibliographies; Calculators; Computer Science Education; Computers; Educational Technology; Elementary School Mathematics; Elementary Secondary Education; Mathematical Vocabulary; Mathematics Curriculum; Mathematics Education; Mathematics Instruction; Problem Sets; Problem Solving; Resource Materials; Science Education; Secondary School Mathematics; Guides, Non-Classroom.